Investigation of the closed kinetic chain upper extremity stability test in elite canoe/kayak slalom athletes - Powell, A.; Williamson, S.; Heneghan, N. R.; Horsley, I. (Physical Therapy in Sport, 2020)
Arm-length was positively correlated with the CKCUEST and normalised-CKCUEST. Arm-length was not correlated with the modified-CKCUEST. There was a significant difference between narrow/wide hand positions scores. The CKCUEST distance should be modified to arm length pre-testing. Objective: To investigate the correlation of arm length with different CKCUEST measures and determine if a modification of the test position (modified-CKCUEST), or normalisation of the CKCUEST (normalised-CKCUEST) score after testing, control for arm length most effectively. Study design: Quasi Experimental. Setting: British Canoe Slalom National Training Centre. Participants: Thirteen (5 male, 8 female) asymptomatic national squad canoe/kayak slalom athletes were recruited during winter profiling. Main outcome measure: Three measures of the CKCUEST were investigated. The CKCUEST, hands 36 inches apart; modified-CKCUEST, hands arm width apart (measured as C7 spinous process to tip of middle finger); and normalised-CKCUEST (measured as CKCUEST score/arm length). Results: A significant positive correlation was found between arm length and the CKCUEST score (r = 0.807; p = 0.001) and normalised-CKCUEST score (r = 0.654; p = 0.015). No significant correlation was found between the modified-CKCUEST score and arm length (p = 0.745). A statistically significant difference between narrow and wide hand positions, greater than the minimal detectable change, was found (p = 0.000). Conclusions: Arm length has a significant impact on CKCUEST score. The modified-CKCUEST score corrected for arm length where the normalised-CKCUEST score did not. Modifying the CKCUEST to individual anthropometrics needs to be performed pre-testing when comparisons are being made between individuals or groups.